2004
DOI: 10.1364/opex.12.000473
|View full text |Cite
|
Sign up to set email alerts
|

Pulse trains produced by phase-modulation of ultrashort optical pulses: tailoring and characterization

Abstract: In this paper, creation of pulse doublets and pulse trains by spectral phase modulation of ultrashort optical pulses is investigated. Pulse doublets with specific features are generated through step-like and triangular spectral phase modulation, whereas sequences of pulses with controllable delay and amplitude are produced via sinusoidal phase modulations. A temporal analysis of this type of tailored pulses is exposed and a complete characterization with the SPIDER technique (Spectral Phase Interferometry for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…When a sinusoidal phase φ(ω) is applied to this pulse, it results in a pulse train with a temporal dependence of the electric field given by [29]:…”
Section: Fig 3a Displays the Eo Signals S(τ)mentioning
confidence: 99%
See 2 more Smart Citations
“…When a sinusoidal phase φ(ω) is applied to this pulse, it results in a pulse train with a temporal dependence of the electric field given by [29]:…”
Section: Fig 3a Displays the Eo Signals S(τ)mentioning
confidence: 99%
“…So, by playing on the modulation strength a one can control, to some extend, the weight of the different pulses of the train. More precisely, the evolution of |J m (a)| is the following [29]: except for |J 0 |, it increases when a is varied from 1.25 to 2.65, leading to an enhancement of the number of pulses in the train. Hence, increasing a will lengthen the THz pulse duration and lead to a narrower spectrum, this regardless of the repetition rate F rep .…”
Section: Fig 3a Displays the Eo Signals S(τ)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the particular case when ω n = ω 0 , an explicit Fourier transform has been found [6] and the temporal electric field has the following form,…”
Section: Spectral Phase Modulation Of Single Pulsementioning
confidence: 99%
“…In principle, such spectral phase and amplitude filtering techniques can produce almost any arbitrary pulse shape. Recently Renard et al [6] demonstrated that substantial control over the pulse shape can be achieved by shaping of the phase only.…”
Section: Introductionmentioning
confidence: 99%